‘Tilik’: A Study of Power Among Javanese Women Through Gossip - Putri Rindu Kinasih (IAIN MADURA, 2021)
Gossip plays a crucial part in our communicative and social behavior as it is thought to be a manifestation of any ‘ordinary’ everyday life. Interestingly, the portrayal of gossip in Javanese culture can be found in the recent viral short movie Tilik (The Ladies on Top). Unfortunately, contemporary interpretations and discussions about Bu Tejo often focus only on what gossip is about and its negative effect on the image of women. None of them observed the relation between gossip and power. Thus, the study aims to analyze gossip in Tilik movie by using the concept of power among Javanese women. The writer used the qualitative method. The writer focused on the theory of gossip and power; and used the concept of power among Javanese women proposed by Handayani and Novianto. This research revealed that gossip in Tilik becomes the weapon of choice in the female arsenal due to the rivalry between Bu Tejo and Dian. Bu Tejo’s negative attitude towards Dian can be seen as a political tactic for Javanese women, and the personal is political. Lastly, the acts of gossiping in the movie match with the concept of how Javanese women play the game of power through srawung (socialization).